Análisis de la aplicación de barreras arancelarias a las importaciones ecuatorianas: caso textil y calzado - Giler Mejía, Glenda Lichet (2010)
This document presents a tributary and economic analysis on the effect produced by the changes in foreign commercial policies in regards to the decisions of the agents of the Ecuadorian economy in order to verify at what extent local industry has been enhanced. Whit the objective of estimating specific effects, the analysis focuses on the measures on imports of textiles, leather goods and footwear, from 1996 to 2010. To analyze the economic impact on the changes of trade policies and to verify whether it meets the objectives of the government's economic program is necessary to work with the Armington’s import substitution elasticities. Finally, the analysis incorporates the effects on tax collection to assess the impacts on their payment. The Armington substitution elasticities estimated for Ecuador at the level of the Supply-Use table fluctuates between 0,343 and 0,788 for the footwear and textile industry respectively. These values suggest that the relationship between imported and domestic goods in the case of these industries is low replacement capacity, which means they are not perfect substitutes.